Comparison of Salivary and Serum Enzyme Immunoassays for the Diagnosis of Helicobacter pylori Infection - John M Embil; Shurjeel H Choudhri; Gerry Smart; Thomas Aldor; Norman M Pettigrew; Gordon R Grahame; Magdy R Dawood; Charles N Bernstein (Canadian Journal of Infectious Diseases)
Infection with Helicobacter pylori has been established as an important risk factor for the development of peptic ulcer disease, gastritis and gastric cancer. The diagnosis of H pylori infection can be established by invasive or noninvasive techniques. Two noninvasive enzyme immunoassays (EIAs) for antibody detection – HeliSal and Pylori Stat – were compared with histology. Both assays detect immunoglobulin (Ig) G directed against purified H pylori antigen. The test populations consisted of 104 consecutive patients scheduled for upper gastrointestinal endoscopy. Of these patients, 97 (93%) had symptoms compatible with peptic ulcer disease. Saliva and serum were collected simultaneously at the time of endoscopy. Salivary EIA had a sensitivity of 66%, specificity of 67%, positive predictive value of 67% and negative predictive value of 66% compared with the serum EIA, where the results were 98%, 48%, 64% and 96%, respectively. Although the salivary EIA is an appealing noninvasive test, it was not a sensitive and specific assay. The serum EIA also lacked specificity, but was highly sensitive with a good negative predictive value. Although a negative serum EIA rules out H pylori infection, a positive result must be interpreted in the clinical context and confirmed with a more specific measure.